Perceived Usability Evaluation of TikTok Shop Platform Using the System Usability Scale - Purwandani, Indah; Syamsiah, Nurfia Oktaviani; Siti Nurwahyuni (Politeknik Ganesha Medan, 2023)
The popularity of TikTok is getting higher because from the start TikTok is a platform that provides a new experience that combines the experience of social media as well as transacting online.TikTok allows businesses to market their products in as creative a form as possible, such as making videos and building a community with their market share. TikTok is an application that plays an important role in paid promotional media, which is of course directly related to digital marketing carried out by business people in the e-commerce sector. In this research, the author wants to know the usability of the TikTok Shop feature as an e-commerce feature that has recently become increasingly popular in society. The System Usability Scale (SUS) will be used to test whether the TikTok application, especially the TikTok Shop feature. The standard SUS version has 10 instruments. The accuracy value is then measured using acceptable rage, grade scale and adjective ratings System Usability Scale (SUS). Based on questionnaire data collected from 49 respondents, it was found that 10.6 percent of the respondents were male and 93.6 percent of the respondents were female. The accuracy value of 79.49 is included in the acceptability ranges acceptable category, meaning that the TikTok Shop platform can be accepted by users, getting a C grade scale means it is quite good and is included in the adjective ratings excellent category.